Copy Number, mRNA Expression Analysis and Clinical Significance of p53 Gene in Bangladeshi Breast Cancer Patients - Nelofar Yasmin; Md Abdul Auwal; Rabeya Khatun; Tasnima Kamal; Md Rashel Mollah; Al-Amin Hossain; Chandan Barai; Azadur Rahman Bhuiyan; Md Ashraful Islam; Zinnat Ara Moni; Asma Ul Husna Biswas; Nousin Taslima Ferdous; et al. (TAJ: Journal of Teachers Association, 2026)
The p53 gene also known as the tumor protein gene 53 situated on the short arm of chromosome 17. It is a tumor suppressor gene that regulates cell division and cell death and is involved in many malignancies, including breast cancers. Herein, we aim to assess the copy number and expression of the p53 gene in breast cancer patients of Bangladesh. Also, the clinical significance p53 copy number variation and mRNA expression was analyzed. The prevalence of low copy number variation of the p53 gene was 67.04% (n=59/88), followed by high copy number variation at 19.31% (n=17/88) and normal copy number variation at 13.63% (n=12/88). Also, the p53 copy number is significantly lower in cancer samples when compared to those of non-cancerous samples (p=0.006). Importantly, the proportion of low gene expression was 58.00% (n=51/88) which was significantly greater than high gene expression at 30.70% (n=27/88) and normal gene expression at 11.40% (n=10/88). Similarly, significant downregulation of p53 mRNA expression was noted in cancer samples in comparison to those of non-cancerous samples (p < 0.0001). The reduced expression of the p53 gene is associated with larger tumor size (p=0.03), regional lymph node involvement (p=0.04), higher histological tumor grade (p=0.003) and advanced cancer stages (p=0.04) of cancer patients. A statistically significant (p=0.001) positive association (r=0.36) was observed between p53 gene expression and copy number variation among the patients. Thus, the p53 could play a crucial role in the pathogenesis of breast cancer and has the potential to be used as a diagnostic and prognostic marker.